2010
DOI: 10.1016/j.ejso.2009.05.009
|View full text |Cite
|
Sign up to set email alerts
|

HERG1 gene expression as a specific tumor marker in colorectal tissues

Abstract: Introduction: Colorectal carcinomas exhibit a frequent recurrence after curative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 20 publications
0
28
0
2
Order By: Relevance
“…These results provide important clues for the potential pharmacological use of hERG modulators in cancer treatment. [18][19][20] ZC88 is a novel compound designed and synthesized by our institute based on a 4-aminopiperidine scaffold. Previous study showed that ZC88 exhibited a marked N-type calcium channel blockage.…”
Section: Discussionmentioning
confidence: 99%
“…These results provide important clues for the potential pharmacological use of hERG modulators in cancer treatment. [18][19][20] ZC88 is a novel compound designed and synthesized by our institute based on a 4-aminopiperidine scaffold. Previous study showed that ZC88 exhibited a marked N-type calcium channel blockage.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, expression of hERG1 isoforms is elevated in primary human cancers, suggesting that this apparent upregulation is not due simply to altered gene expression with adaptation to in vitro culture conditions. Thus, hERG1 channels are overexpressed in endometrial adenocarcinoma (Cherubini et al, 2000), colorectal cancer (Lastraioli et al, 2004;Dolderer et al, 2010), gastric cancer (Shao et al, 2008), glioblastoma multiforme, myeloid leukemias , and acute lymphoblastic leukemias Smith et al, 2002); but expression is below detectable limits in noncancerous tissues. Interestingly, hERG1 expression in tumors correlates with metastatic cancers and a poorer prognosis (Lastraioli et al, 2004;Masi et al, 2005;Ding et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the disparate Tl þ flux and APPC results is not clear; however, our results indicate that ciclopirox clearly modulates hERG channel activity. Since hERG channels are overexpressed in many tumor cells and modulation of hERG channel activity has resulted in inhibition of tumor growth, 44,45 it is tempting to speculate that the antitumor activity of ciclopirox is at least partially due to modulation of hERG channel activity.…”
Section: Resultsmentioning
confidence: 99%